Government Migration to Cloud Ecosystems : Multiple Options, Significant Benefits, Manageable Risks - World Bank (Washington, DC, 2022)
Migrating from legacy IT infrastructure and data storage to cloud services can yield enormous benefits for governments: it can save governments money; increase the integrity, quality, and speed with which they deliver services; and provide access to the most advanced analytical tools and cybersecurity features available. These benefits have spurred a shift by governments across the globe away from legacy information technology (IT) systems, and towards cloud solutions, including public cloud services.